2021
DOI: 10.4314/gjpas.v27i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mineral composition of proceessed cheese, soy and nunu milks consumed in Abuja and Keffi metropolises of Nigeria

Abstract: Milk and its products are needed for proper body building. Processed cheese, nunu and soy milk consumed within Abuja and Keffi metropolises were analyzed for their mineral contents. X1, Y1, Z1 represents soy milk, nunu and cheese from Abuja metropolis while X2, Y2, Z2 represents sample from Keffi metropolis respectively. Calcium (265.53±0.25 mg/mL), iron (1.19±0.92 mg/mL), potassium (162.77±0.02 mg/mL) were found to be higher in cheese milk (Z1) from Abuja than that (225.82±0.13 mg/mL, 1.05±0.60mg/mL and 130.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
0
1
Order By: Relevance
“…The results obtained in this research fall within the value stipulated above. It also agrees with the result obtained by Okpara et al (2021) who reported a range of 40.02-43.85 mg/100g, and Udeozor (2012) who reported the calcium content of unfortified soy milk to be 44.5±0.3368. The variation in the result obtained in this work could be attributed to the processing methods and conditions used.…”
Section: Mineral Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in this research fall within the value stipulated above. It also agrees with the result obtained by Okpara et al (2021) who reported a range of 40.02-43.85 mg/100g, and Udeozor (2012) who reported the calcium content of unfortified soy milk to be 44.5±0.3368. The variation in the result obtained in this work could be attributed to the processing methods and conditions used.…”
Section: Mineral Analysissupporting
confidence: 92%
“…These variations could be attributed to the processing method, technology employed in the production and the rehydration time for the soymilk produced from ISP. Apart from sample CBS, the values obtained in this work is higher than the 32mg/100g reported by Udeozor (2012), 14-21 reported by Asuquo and Antai (2017), 4.05-17.97 (mg/mL) obtained by Okpara et al 2021. Similarly, Nwoke et al, (2015 reported 53.76 to 54.83.…”
Section: Mineral Analysiscontrasting
confidence: 53%